Antitumor effect of novel anti‐podoplanin antibody NZ‐12 against malignant pleural mesothelioma in an orthotopic xenograft model. Issue 9 (25th August 2016) - Abe, Shinji; Kaneko, Mika Kato; Tsuchihashi, Yuki; Izumi, Toshihiro; Ogasawara, Satoshi; Okada, Naoto; Sato, Chiemi; Tobiume, Makoto; Otsuka, Kenji; Miyamoto, Licht; Tsuchiya, Koichiro; Kawazoe, Kazuyoshi; et al.
Abstract : Podoplanin (aggrus) is highly expressed in several types of cancers, including malignant pleural mesothelioma (MPM). Previously, we developed a rat anti‐human podoplanin mAb, NZ‐1, and a rat–human chimeric anti‐human podoplanin antibody, NZ‐8, derived from NZ‐1, which induced antibody‐dependent cellular cytotoxicity (ADCC) and complement‐dependent cytotoxicity against podoplanin‐positive MPM cell lines. In this study, we showed the antitumor effect of NZ‐1, NZ‐8, and NZ‐12, a novel rat–human chimeric anti‐human podoplanin antibody derived from NZ‐1, in an MPM orthotopic xenograft SCID mouse model. Treatment with NZ‐1 and rat NK (CD161a + ) cells inhibited the growth of tumors and the production of pleural effusion in NCI‐H290/PDPN or NCI‐H226 orthotopic xenograft mouse models. NZ‐8 and human natural killer (NK) (CD56 + ) cells also inhibited tumor growth and pleural effusion in MPM orthotopic xenograft mice. Furthermore, NZ‐12 induced potent ADCC mediated by human MNC, compared with either NZ‐1 or NZ‐8. Antitumor effects were observed following treatment with NZ‐12 and human NK (CD56 + ) cells in MPM orthotopic xenograft mice. In addition, combined immunotherapy using the ADCC activity of NZ‐12 mediated by human NK (CD56 + ) cells with pemetrexed, led to enhanced antitumor effects in MPM orthotopic xenograft mice. These results strongly suggest that combination therapy with podoplanin‐targeting immunotherapy using both NZ‐12 and pemetrexed might provide an efficacious therapeutic strategy for the treatment of MPM. Abstract : Treatment of NZ‐1, NZ‐8, and NZ‐12 with NK cells induce therapeutic antitumor effect due to ADCC activity in MPM orthotopic xenograft mice models.In addition, treatment of both NZ‐12‐mediated immunotherapy and pemetrexed led to enhanced antitumor effects in MPM orthotopic xenograft mice. These data strongly suggested that NZ‐12 is an effective antibody against MPM.